Residential heating system selection using the generalized Choquet integral method with the perspective of energy - Ozdemir, Yavuz; Ozdemir, Sahika (SAGE PUBLICATIONS LTD, 2019)
Using energy effectively is one of the most important issues and problems that countries should take up. As a parallel of increasing energy demands worldwide and still mostly using fossil fuels, energy saving issues have gained much importance in recent years for all areas of life. It is a fact that construction also plays an important role in the emergence of the energy and environmental problem that we see as the problem of our centenary. As buildings consume about 40% of the world's annual energy consumption globally, this study will focus on the evaluation of residential heating system alternatives using the generalized Choquet integral method with trapezoidal fuzzy numbers. The main contribution of this paper is to determine the interdependency among main criteria and subcriteria, the nonlinear relationship among them and the environmental uncertainties while prioritizing residential heating system alternatives using the generalized Choquet integral method with the experts' view. To the authors' knowledge, this will be the first interdisciplinary study that uses the generalized Choquet integral method for residential heating systems.
Keywords: Choquet integral; decision-making; energy saving; environment; heating systems; housing warming; MULTICRITERIA DECISION-MAKING; EVALUATE; Environmental Sciences & Ecology